Evaluation of the treatment after default rates in a tuberculosis dispensary in 10 years period and the effect of directly observed treatment - (:unkn) unknown (Yuzuncu Yil Universitesi Tip Fakultesi, 2014)
We aimed to evaluate that defaulting from tuberculosis (TB) treatment rates and patient characteristics in our dispensary in 10 years period. The files of patients with treatment after default between 1997 and 2006 were retrospectively analysed. Statistical analyses were made using SPSS package programme. Between 1997 and 2006 a total of 3142 patients undergoing treatment, 67 (2.13%) had defaulting from treatment. Treatment after default rates with respect to years were 3.2% in 1997, 2.8% in 1998, 3.0% in 1999, 3.0% in 2000, 2.9% in 2001, 3.4% in 2002, 1.4% in 2003, 1.0% in 2004, 0.5% in 2005 and 1.3% in 2006. The mean period for treatment after default was 2.4±1.6 months. When patients were grouped into two with respect to treatment periods (1997-2001 and 2002-2006); age, gender, marital status, education status, the number of household contacts, the mean treatment after default months, the type of the disease, demonstrated no statistically significant difference. The first group had greater mean of the treatment after default rate than the second group (p<0.001) It was found out that treatment after default rates in our dispensary in 10 years period is less than 5% which is targeted by World Health Organization (WHO). No differences about social and clinical characteristics of cases were detected. However, decline in treatment after default rates was found to be statistically significant with application of directly observed treatment (DOT). Close monitoring of patients and to be sensitive for their needs, may contribute to decrease the default rates from TB treatment.
Keywords: Patient compliance; Treatment; Tuberculosis